Story People: Stó:lō-State Relations and Indigenous Literacies in British Columbia, 1864–1874 - Harvey, Megan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2013)
The Stó:lō are a group of approximately 28 different communities, which share a common language and culture in what is now generally known as the Lower Fraser Valley of southwestern British Columbia. Between 1864 and 1874, Stó:lō and neighbouring tribes presented four petitions to the colonial and (after 1871) federal government. The survival of so many Indigenous texts from this era that speak directly to the state offers a rare interpretive opportunity. In a relatively brief period of time, colonial and then provincial authorities rapidly obtained increased control over both lands and people in the emerging province. Simultaneously, Halkomelem-speaking peoples in the region swiftly developed new cultural literacies, among which was a facility with one of the central technologies of settler power: writing. As we will see in the following discussion, the earliest forms of Indigenous writing we have for this period are about land and Stó:lō peoples’ relationships with settler authorities. This series of petitions traces an important shift in settler-Indigenous relations, while also revealing a great deal about Indigenous ideas around literacy and how settler appropriation of Stó:lō land was challenged from the very earliest days. Throughout, a focus on story demonstrates how the struggles over land that have characterized Indigenous-state relations in British Columbia are also, inextricably, a struggle for narrative power.